The value of spatial experience and group size for ant colonies in direct competition. (29th June 2022) - Subach, Aziz; Avidov, Bar; Dorfman, Arik; Bega, Darar; Gilad, Tomer; Kvetny, Mark; Reshef, May Hershkovitz; Foitzik, Susanne; Scharf, Inon
Abstract: Animals often search for food more efficiently with experience. However, the contribution of experience to foraging success under direct competition has rarely been examined. Here we used colonies of an individually foraging desert ant to investigate the value of spatial experience. First, we trained worker groups of equal numbers to solve either a complex or a simple maze. We then tested pairs of both groups against one another in reaching a food reward. This task required solving the same complex maze that one of the groups had been trained in, to determine which group would exploit better the food reward. The worker groups previously trained in the complex mazes reached the food reward faster and more of these workers fed on the food than those trained in simple mazes, but only in the intermediate size group. To determine the relative importance of group size versus spatial experience in exploiting food patches, we then tested smaller trained worker groups against larger untrained ones. The larger groups outcompeted the smaller ones, despite the latter's advantage of spatial experience. The contribution of spatial experience, as found here, appears to be small, and depends on group size: an advantage of a few workers of the untrained group over the trained group negates its benefits. Graphical Abstract: Groups of ant workers trained to solve a complex maze win the competition against other groups untrained in the same maze, reflected in faster food discovery and more workers feeding on the food reward. Still, larger untrained groups are more successful than smaller trained groups. The contribution of spatial experience, at least under the tested framework, is small, and depends on group size.